Mainshock–aftershock low-cycle fatigue damage evaluation of performance-based optimally designed steel moment frames. (15th June 2021) - Ghaderi, Masoud; Gholizadeh, Saeed
Highlights: Total cost–based seismic optimization of SMFs. Low-cycle fatigue assessment of optimally designed SMFs for seismic sequence. The optimal designs are vulnerable to mainshock-aftershock low-cycle fatigue damage. A procedure is proposed to design safe SMFs against mainshock-aftershock low-cycle fatigue damage. Abstract: Considering the widespread damages of connections in steel moment frame (SMF) structures due to destructive earthquakes, seismic assessment of these structures for cumulative low-cycle fatigue (LCF) is of utmost importance and must be carefully taken into account in the design process of SMFs. To calculate the LCF damage index for SMFs, the Palmgren-Miner's rule is applied on the history of relative drift of the stories based on non-linear response history analysis and existing experimental fatigue curves. On the other hand, repeated earthquakes strongly affect the inelastic response of structures and can increase building vulnerability. Therefore, the primary objective of this study is to numerically assess the mainshock-aftershock LCF damage index for performance-based optimally designed SMFs. Two illustrative design examples of 6- and 12-story SMFs are presented and designed for optimal initial and total costs in the context of performance-based design. The LCF damage index is evaluated for these structures by conducting nonlinear response-history analysis for a suite of real strong multiple earthquakes. The results showed that the optimally designed SMFs are highly vulnerable against LCF damage due to mainshock-aftershock seismic sequences. Subsequently, a simple procedure is proposed to increase the safety of optimally designed SMFs against the LCF damage. To this end, performance-based optimization process is performed for 6- and 12-story SMFs by considering higher seismic confidence levels and the results demonstrate the effectiveness of this strategy in controlling the LCF damage of SMFs caused by seismic sequences.